Hemodynamic profile of patients with severe aortic valve stenosis and atrial fibrillation versus sinus rhythm. (15th July 2020) - Weber, Lukas; Rickli, Hans; Ammann, Peter; Taramasso, Maurizio; Brenner, Roman; Ehl, Niklas F.; Buser, Marc; Haager, Philipp K.; Maisano, Francesco; Maeder, Micha T.
Abstract: Background: In patients with severe aortic stenosis (AS), atrial fibrillation (AF) is associated with increased long-term mortality after aortic valve replacement (AVR), which may be due to unfavorable hemodynamics in AF. We aimed to analyze the hemodynamic profile of patients with severe AS and AF versus sinus rhythm (SR). Methods: We performed cardiac catheterization in 486 patients (age 74 ± 10 years, 58% males) with severe AS [indexed aortic valve area 0.41 ± 0.13 cm 2, left ventricular ejection fraction 58 ± 12%]: 50 patients had AF, and 436 patients had SR. All patients underwent surgical ( n = 350) or transcatheter ( n = 136) AVR. Results: Despite similar indexed aortic valve area (0.41 ± 0.11 vs. 0.41 ± 0.12 cm 2 /m 2 ; p = 0.45) patients with AF had lower left ventricular ejection fraction, larger left atrial size, lower tricuspid annular plane systolic excursion, higher mean pulmonary artery pressure (34 ± 13 vs. 24 ± 9 mmHg), mean pulmonary artery wedge pressure (mPAWP; 22 ± 8 vs. 15 ± 7 mmHg), and pulmonary vascular resistance (2.8 ± 1.9 vs. 2.0 ± 1.3 Wood units) and lower stroke volume index (26 ± 9 vs. 37 ± 10 ml/m 2 ) than patients with SR ( p < 0.05 for all). Patients with AF and SR had a different mPAWP-left ventricular end-diastolic pressure (LVEDP) relationship with higher mPAWP in AF and higher LVEDP in SR. After a median follow-up of 49 (interquartile range, 35–64) months post-AVR patients with AF ( p = 0.05) and patients with a larger difference between mPAWP and LVEDP ( p = 0.005) had higher mortality. Conclusions: Patients with severe AS and concomitant AF have a distinct and significantly worse hemodynamic profile compared to patients with SR associated with worse clinical outcome. Highlights: Patients with AS and AF have worse hemodynamics compared to those with SR. In AS patients, those with AF and SR have a different mPAWP to LVEDP relationship. Patients with AS and AF have higher mortality after valve replacement versus SR.